Resource recovery from waste coffee grounds using ultrasonic-assisted technology for bioenergy production - Mofijur M.; Kusumo F.; Rizwanul Fattah I.M.; Mahmudul H.M.; Rasul M.G.; Shamsuddin A.H.; Mahlia T.M.I. (MDPI AG, 2023)
Absorption spectroscopy; Biodiesel; Hexane; Light absorption; Organic solvents; Spectrum analysis; Transesterification; Biodiesel feedstock; Bioenergy productions; Extraction process; Optimal conditions; Response surface methodology; Solid to solvent ratios; Soxhlet techniques; Transesterification process; Solvent extraction